EFFECTIVENESS AND IMPROVE THE MORALE INFORMATION SERVICES FOR STUDENTS AT MTS MUHAMMADIYAH 10 KOTANOPAN ACADEMIC YEAR 2015-2016 - Anas Munandar Matondang (Universitas Muhammadiyah Tapanuli Selatan, 2016)
The study is based on the problem still lower students' knowledge of moral development in the school environment in general, the researchers are